Using Semantic Similarity to Improve Information Discovery in Spatial Data Infrastructures - de Andrade, Fabio G.; Baptista, Cláudio de S. (Journal of Information and Data Management, 2011)
In the recent years, several works have been proposed with an approach to the use of semantics to improve the process of discovering geographic resources offered by spatial data infrastructures. However, semantic queries may return a large number of results, what causes the necessity for e?cient ways to evaluate the relevance of each retrieved result. This article proposes a framework that uses ontologies and thematic relevance to suggest a measurement that allows evaluating how relevant is each resource offered by the infrastructure to the user’s query. This feature allows the results retrieved in a query to be organized through a ranking, in such a way that the most relevant resources are presented to the user ?rst.